PENGARUH HEALTH EDUCATION TERHADAP PENGETAHUAN IBU TENTANG PIJAT BAYI DI PMB ERNA PENIWATI - Ambika Kurnia Mustikawati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2022)
Haemorrhoids are common in pregnant women in the second or third trimester of pregnancy. Increased intra-pressure due to fetal growth and changes in the hormone progesterone causes the hemorrhoidal veins to become wide. Pregnancy hemorrhoids are temporary hemorrhoids which means they will disappear some time after delivery, but can cause a very uncomfortable feeling, itching around the anus and even bleeding during bowel movements. Therefore, self care is needed, one of them is the sitz bath method. The design in this study is a pre-experiment with the One Group Pretest-Posttest design approach. The population in this study were all mothers with hemorrhoids who participated in the pregnant class at Balong Health Center for the period of 1-28 February 2020, a total of 37 people. The sampling method used accidental sampling of 31 people. Instrument with quesioner Statistical test using the Wilcoxon Signed-Rank Test through the SPSS program with α = 0.05. The result of knowledge of mothers about Sitz Bath Therapy in the Work Area of ​​Puskesmas Balong, Ponorogo Regency, before health education was carried out, most of them were 16 respondents (51.6%) had sufficient knowledge and after health education was carried out most of them 18 respondents (58.1%) had good knowledge. There is an effect of health education on maternal knowledge about Sitz Bath Therapy in the working area of ​​ Health Center Balong, Ponorogo with a p value of 0.000 ≤ α 0.05. The role of health workers as educators is better to carry out routine health education during the provision of care, especially regarding the method of sitz bath therapy so that targets can better understand and be able to overcome hemorrhoid problems that occur in pregnancy.